1992
DOI: 10.1007/bf00326130
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive resection for advanced pancreatic carcinoma

Abstract: An aggressive pancreatectomy was performed on a 53 year old Japanese man with advanced cancer of the pancreas. The tumor originated from the body of the pancreas and invaded the stomach, duodenum, left kidney, transverse colon and common hepatic artery. An unexpected cancer was also found in the head of the pancreas during the operation. Therefore, total pancreatectomy, total gastrectomy, left adrenonephrectomy, resection of the left transverse colon and dissection of the regional lymph nodes were performed. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…More recent series [10,18,[32][33][34] have shown that these operations can be performed with a moderate risk in patients over age 70 as well. In the present study an age over 70 years did not represent an absolute contraindication for surgery (nine resections performed) and involved only moderate morbidity (a single, albeit fatal, complication).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent series [10,18,[32][33][34] have shown that these operations can be performed with a moderate risk in patients over age 70 as well. In the present study an age over 70 years did not represent an absolute contraindication for surgery (nine resections performed) and involved only moderate morbidity (a single, albeit fatal, complication).…”
Section: Discussionmentioning
confidence: 99%
“…Elderly age has long been considered a contraindication for pancreatic resection based on series reported in the literature [23,31] that indicated markedly increased morbidity and mortality in patients over 65 to 70 years of age. More recent series [10,18,[32][33][34] have shown that these operations can be performed with a moderate risk in patients over age 70 as well. In the present study an age over 70 years did not represent an absolute contraindication for surgery (nine resections performed) and involved only moderate morbidity (a single, albeit fatal, complication).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation